INCIDENCE OF DENGUE HEMORRHAGIC FEVER AFTER THE EARTHQUAKE IN CENTRAL SULAWESI INDONESIA (Proceedings of the International Conference on Public Health, 2021)
The earthquake can cause a potential transmission of the disease after the disaster. One ofthe infectious diseases that could potentially be a post-earthquake outbreak is Dengue HemorrhagicFever (DHF). The earthquake, followed by a tsunami and liquefaction that struck Palu's city, Sigi'sregency, and the regency of Donggala in Central Sulawesi in September 2018, led to the increasedtransmission of the dengue hemorrhagic fever disease in all three regions. This research aims todetermine the incidence rate of DHF in the affected areas of the earthquake disaster in CentralSulawesi. The data used involved the number of DHF cases before and after the earthquake (2015-2019) in Palu, Sigi, and Donggala. The data was obtained from the Health Office of CentralSulawesi Province. The results of the analysis showed that the Incidence Rate (IR) of DHF in 2019was 165.94 (Palu), 77.13 (Sigi), and 62.86 (Donggala). Dengue Hemorrhagic Fever's IR increasedafter the earthquake in Palu, Sigi, and Donggala in 2019 that marked the outbreak of DHF in all threeregions. The highest increase in the DHF cases was found in Palu. The efforts to improve the healthsystem are needed by strengthening DHF diagnosis, DHF case reporting, vector surveillance, activetemephos distribution, and community empowerment to reduce DHF vector breeding sites.
Keywords: Earthquake, DHF, Outbreak